New insight into sugarcane industry waste utilization (press mud) for cleaner biobutanol production by using c. acetobutylicum nrrl b-527 - Nimbalkar, Pranhita R.; Khedkar, Manisha A.; Gaikwad, S. G.; Chavan, Pramod V.; Bankar, Sandip B. (Applied Biochemistry and Biotechnology, 2017)
In the present study, press mud, a sugar industry waste, was explored for biobutanol production to strengthen agricultural economy. The fermentative production of biobutanol was investigated via series of steps, viz. characterization, drying, acid hydrolysis, detoxification, and fermentation. Press mud contains an adequate amount of cellulose (22.3%) and hemicellulose (21.67%) on dry basis, and hence, it can be utilized for further acetone-butanol-ethanol (ABE) production. Drying experiments were conducted in the temperature range of 60–120 °C to circumvent microbial spoilage and enhance storability of press mud. Furthermore, acidic pretreatment variables, viz. sulfuric acid concentration, solid to liquid ratio, and time, were optimized using response surface methodology. The corresponding values were found to be 1.5% (v/v), 1:5 g/mL, and 15 min, respectively. In addition, detoxification studies were also conducted using activated charcoal, which removed almost 93–97% phenolics and around 98% furans, which are toxic to microorganisms during fermentation. Finally, the batch fermentation of detoxified press mud slurry (the sample dried at 100 °C and pretreated) using Clostridium acetobutylicum NRRL B-527 resulted in a higher butanol production of 4.43 g/L with a total ABE of 6.69 g/L. © 2017 Springer Science+Business Media New York Author keywords
Keywords: Acetone; Acetone butanol ethanols; Acidic pre treatments; Agriculture; Biobutanol; cellulose; Clostridium acetobutylicum; Detoxification; Drying; Drying Fermentation; FermentationSpoilage; Fermentative production; Pre-treatment; Press mud; Press mud Pretreatment; Response surface methodology; Sugar industry; Sulfur determination

Process intensification strategies for enhanced holocellulose solubilization: Beneficiation of pineapple peel waste for cleaner butanol production - Khedkar, Manisha A.; Nimbalkar, Pranhita R.; Kamble, Sanjay P.; Gaikwad, Shashank G.; Chavan, Prakash V.; Bankar, Sandip B. (Journal of Cleaner Production, 2018)
Biorefinery sector has become a serious dispute for cleaner and sustainable development in recent years. In the present study, pretreatment of pineapple peel waste was carried out in high pressure reactor using various pretreatment-enhancers. The type and concentration effect of each enhancer on hemicellulose solubilization was systematically investigated. The binary acid (phenol + sulfuric acid) at 180 degrees C was found to be superior amongst other studied enhancers, giving 81.17% (w/v) hemicellulose solubilization in liquid-fraction under optimized conditions. Solid residue thus obtained was subjected to enzymatic hydrolysis that resulted into 24.50% (w/v) cellulose breakdown. Treated solid residue was further characterized by scanning electron microscopy and fourier transform infrared spectroscopy to elucidate structural changes. The pooled fractions (acid treated and enzymatically hydrolyzed) were fermented using Clostridium acetobutylicum NRRL B 527 which resulted in butanol production of 5.18 g/L with yield of 0.13 g butanol/g sugar consumed. Therefore, pretreatment of pineapple peel waste evaluated in this study can be considered as milestone in utilization of low cost feedstock, for bioenergy production. (C) 2018 Elsevier Ltd. All rights reserved.

Solvent extraction of butanol from synthetic solution and fermentation broth: batch and continuous studies - Khedkar, Manisha A.; Nimbalkar, Pranhita R.; Gaikwad, Shashank G.; Chavan, V, Prakash; Bankar, Sandip B. (Separation and Purification Technology, 2020)
Product recovery is one of the essential finishing steps to any commercial fermentation process. In acetone-butanol-ethanol (ABE) fermentation, butanol recovery is quite tedious mainly due to dilute product and multiple byproduct formation in complex media. Among different recovery methods, extraction has attracted considerable attention in biofuel recovery owing to its high selectivity, low energy consumption, and ease of operation. In present work, the butanol extraction performance from synthetic solvent mixture containing ABE was tested in batch and continuous operations using 20% (v/v) decanol in oleyl alcohol. The optimized extraction conditions were then validated using actual fermentation broth to confirm effectiveness of the extraction operation. The distribution coefficient (K-d) and batch extraction efficiency (E) were in the range of 5.60-9.80 and 87.70-86.90% for fermentation broth and synthetic solution, respectively for a given initial concentration of butanol in the aqueous phase. Further, E was relatively improved by supplementing different inorganic salts. Sodium hydroxide (5%, w/v) was highly effective to recover butanol from fermentation broth (E similar to 97.70%) with K-d of 33.10. Besides, the continuous counter current extraction of butanol in a packed column was performed. The volumetric mass transfer coefficient (kLa) was estimated to be 0.025 1/min at an optimized superficial velocity of the aqueous phase (0.28 cm/min) and sodium hydroxide concentration (5%, w/v). Height of the extraction column was estimated to be 28.32 cm using height of transfer unit (HTU) and number of transfer unit (NTU) concept for extraction efficiency of 97.20%. Overall, the present study has demonstrated an enhanced extraction efficiency of butanol from fermentation broth.
Keywords: Biobutanol; Equilibrium stages; Height of transfer unit; liquid-liquid extraction; mass transfer coefficient; Number of transfer unit

Review on microbial 1, 3-propanediol production: Emerging strategies, key hurdles and attainable solutions to re-establish its commercial interest - Nimbalkar, Pranhita R.; Dharne, Mahesh S. (Industrial Crops and Products, 2024)
1,3-propanediol (1,3-PDO) is a vital value-added bi-functional compound that has numerous uses in the industrial sector including the polymer, pharmaceutical, food, and cosmetics industries. 1,3-PDO biosynthesis from renewable resources through green methods has received considerable attention. However, technical difficulties such as low product titer, by-product accumulation, and incomplete substrate consumption impede its sustainable production at the industrial scale. Hence, understanding the overall 1,3-PDO process development with integrated knowledge of techno-economics would help to build more production facilities across the world. In this view, the biotechnological production of 1,3-PDO is systematically reviewed briefing the synthesis routes, microbial strains, metabolic pathways, and fermentation modes along with several purification strategies. The present review also summarizes key hurdles in 1,3-PDO production and discusses the attainable solutions to achieve higher product titer. Finally, the economic viability of 1,3-PDO biosynthesis is described based on the existing research.
Keywords: 3-Propanediol; Fermentation processes; Glycerol; Purification strategies; Techno-economical assessment